2014
DOI: 10.1080/07391102.2014.932310
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo loop refinement and virtual screening of the thyroid-stimulating hormone receptor transmembrane domain

Abstract: Metropolis Monte Carlo (MMC) loop refinement has been performed on the three extracellular loops (ECLs) of rhodopsin and opsin-based homology models of the thyroid-stimulating hormone receptor transmembrane domain, a class A type G protein-coupled receptor. The Monte Carlo sampling technique, employing torsion angles of amino acid side chains and local moves for the six consecutive backbone torsion angles, has previously reproduced the conformation of several loops with known crystal structures with accuracy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 65 publications
(75 reference statements)
0
19
0
Order By: Relevance
“…The strong biochemical and biophysical evidence of TM1 as a potential regional interface for TSHR oligomerization was further supported by BD analysis based on our TMD structure developed from a rhodopsin-based model of the loop regions of the TSHR-TMD (23). While both the homology model and the BD protocol used involved serious approximations, earlier work showed that this technique was capable of predicting actual dimerization surfaces.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…The strong biochemical and biophysical evidence of TM1 as a potential regional interface for TSHR oligomerization was further supported by BD analysis based on our TMD structure developed from a rhodopsin-based model of the loop regions of the TSHR-TMD (23). While both the homology model and the BD protocol used involved serious approximations, earlier work showed that this technique was capable of predicting actual dimerization surfaces.…”
Section: Discussionmentioning
confidence: 91%
“…This led us to map the interfacial contacts on the TMD. To proceed with mapping and prediction of residues that may be involved in TSHR dimer/oligomer formation we generated a new model of the TSHR-TMD by constructing a TMD with extra and intracellular loops (23). Our modeling data predicted that constitutive oligomerization of the TSHR would involve multiple residues in one or more helices and the experimental data were also in favor of multiple interacting sites.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This template was chosen because of the low RMSD values between the backbone of the TM helices of the TSHR model and that of the rhodopsin x-ray crystal structure (33), and fits the experimental parameters previously described (34). The initial homology model of rhodopsin was obtained from the Uniprot server (www.uniprot.org).…”
Section: Docking Of Lead Molecules On the Tshr Transmembranementioning
confidence: 99%